EFEKTIVITAS SIDEDI-DM DENGAN VIDEO TERHADAP TINGKAT PENGETAHUAN USIA DEWASA - Elka Fitri, Dwi; Ovari, Isna; Elfa Yenti, Selvi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Viewed epidemiologically, diabetes mellitus is often not detected and the onset of diabetes mellitus is 7 years of diagnosis, so that early mortality and mortality occur cases that are not detected early. Early detection of diabetes mellitus is a public understanding of early action as an effort to possibly get diabetes mellitus early so that it can be handled adequately, so that diseases and complications can be prevented. The purpose of this study is to determine the effectiveness of diabetes mellitus early detection education (SIDEDI-DM) with video media on the level of knowledge in adulthood in Payung Sekaki District. This research is a quantitative research with a Pre-experimental design, in the form of a One Group Pre-Test Post-Test design. Sampling in this study used purposive sampling with 30 respondents. Data collection using Diabetes Mellitus Early Detection Knowledge questionnaire sheet using Wilcoxon Rank Test. The results of the study before the intervention showed that the highest value was 6 and the lowest score was 2 with an average value of 4.67, as many as 21 people (70.0%) had sufficient knowledge, and as many as 9 people (30.0%) had less knowledge, and none had high knowledge. After being given the intervention, the highest level of knowledge was 10 and the lowest 7 with an average score of 7.97, as many as 30 respondents had high knowledge. Based on the results of the Wilcoxon Rank Test, P-value = 0.000 is smaller than alpha (p < 0.05). The researchers' conclusion is that there is a difference in the average .Keywords: Diabetes Mellitus Early Detection Education (SIDEDI-DM), Knowledge Level